Spatial Stochastic Frontier Models - Rouselle F. Lavado; Erniel B. Barrios (Philippine Institute for Development Studies (PIDS), 2010)
The stochastic frontier model with heterogeneous technical efficiency explained by exogenous variables is augmented with a sparse spatial autoregressive component for a cross-section data, and a spatial-temporal component for a panel data. An estimation procedure that takes advantage of the additivity of the model is proposed, computational advantages over simultaneous maximum likelihood estimation of all parameters is exhibited. The technical efficiency estimates are comparable to existing models and estimation procedures based on maximum likelihood methods. A spatial or spatial-temporal component can improve estimates of technical efficiency in a production frontier that is usually biased downwards.
Keywords: 330; technical efficiency; stochastic frontier; Philippines; spatial externalities; spatial-temporal model; backfitting; Technische Effizienz; Panel; Maximum-Likelihood-Schätzung